Skin Barrier and Autoimmunity—Mechanisms and Novel Therapeutic Approaches for Autoimmune Blistering Diseases of the Skin - Stevens, Natalie E.; Cowin, Allison J.; Kopecki, Zlatko (Frontiers in Immunology, 2019)
One of the most important functions of the skin besides regulating internal body temperature includes formation of the barrier between the organism and the external environment, hence protecting against pathogen invasion, chemical and physical assaults and unregulated loss of water and solutes. Disruption of the protective barrier is observed clinically in blisters and erosions of the skin that form in autoimmune blistering diseases where the body produces autoantibodies against structural proteins of the epidermis or the epidermal-dermal junction. Although there is no cure for autoimmune skin blistering diseases, immune suppressive therapies currently available offer opportunities for disease management. In cases where no treatment is sought, these disorders can lead to life threatening complications and current research efforts have focused on developing therapies that target autoantibodies which contribute to disease symptoms. This review will outline the involvement of the skin barrier in main skin-specific autoimmune blistering diseases by describing the mechanisms underpinning skin autoimmunity and review current progress in development of novel therapeutic approaches targeting the underlying causes of autoimmune skin blistering diseases.